2009
DOI: 10.1090/crmp/047/12
|View full text |Cite
|
Sign up to set email alerts
|

Hecke operators in equivariant elliptic cohomology and generalized moonshine

Abstract: Contents 1. Introduction 1.1. Background on generalized Moonshine 1.2. Background on equivariant elliptic cohomology and statement of results 1.3. Acknowledgements 2. Principal bundles over complex elliptic curves 2.1. The moduli space of principal G-bundles 2.2. Line bundles over M G 2.3. Construction and properties of the Freed-Quinn line bundle L α 2.4. Sections of L α 3. Abelian groups and level structures 3.1. Isogenies 3.2. Duals 3.3. Cyclic groups 4. Symmetric groups and coverings 5. Hopkins-Kuhn-Ravene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…equivariant, with respect to the M 24 -action on the pair (g, h), and it should incorporate the α-twist in the modular transformation. Equivariant versions of Hecke operators acting on modular forms was proposed by Ganter [55] in the context of generalized Monstrous moonshine, and we shall see that this result also applies here after some minor modifications.…”
Section: Twisted Equivariant Hecke Operatorssupporting
confidence: 67%
See 2 more Smart Citations
“…equivariant, with respect to the M 24 -action on the pair (g, h), and it should incorporate the α-twist in the modular transformation. Equivariant versions of Hecke operators acting on modular forms was proposed by Ganter [55] in the context of generalized Monstrous moonshine, and we shall see that this result also applies here after some minor modifications.…”
Section: Twisted Equivariant Hecke Operatorssupporting
confidence: 67%
“…Before we close this section we shall offer a more geometric perspective on the twisted twining genera which will be useful later on. In [55], Ganter showed that the natural home for the Norton series f (g, h; τ ) [19] is the equivariant elliptic cohomology developed in [56]. We shall here give a short review of Ganter's perspective, adapted to the case of Jacobi forms on (2.26) ¶ This should really be a moduli stack but we ignore this technical point; see [55] for a more precise description.…”
Section: Geometric Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…The description of A G as a conformal boundary condition for Z(Vect ω [G]) explains the relationship between anomalies and the multipliers for twisted-twining genera [GPRV13, Section 3]. Indeed, following [Gan09], let M = M 1 denote the moduli stack of elliptic curves and let M G denote the moduli stack of elliptic curves equipped with a principal G-bundle, and let L ω denote the line bundle thereon constructed from ω. The Hilbert space that the Dijkgraaf-Witten theory Z(Vect ω [G]) assigns to an elliptic curve E is the fiber over E ∈ M of the pushforward of L ω along M G → M. The "twisted-twining genera" are the (genus-one) conformal blocks of A G ; abstract nonsense of boundary field theories says that they are sections of L ω .…”
Section: Orbifolds Of Conformal Field Theoriesmentioning
confidence: 99%
“…We have also been inspired by the idea that 3-cocycles G × G × G → U(1) (when G is finite, these represent classes in H 4 (G; Z)) can explain and predict some features of moonshine [4,16,17,18]. Such a cocycle can arise as the gauge anomaly of a G-action on a conformal field theory.…”
Section: Motivationmentioning
confidence: 99%